The Tea Party three principles - Foley, Elizabeth Price 1965- (Cambridge Univ. Press, 2012)
"In The Tea Party: Three Principles, constitutional law professor Elizabeth Price Foley takes on the mainstream media's characterization of the American Tea Party movement, asserting that it has been distorted in a way that prevents meaningful political dialogue and may even be dangerous for America's future. Foley sees the Tea Party as a movement of principles over politics. She identifies three "core principles" of American constitutional law that bind the decentralized, wide-ranging movement: limited government, unapologetic U.S. sovereignty, and constitutional originalism. These three principles, Foley explains, both define the Tea Party movement and predict its effect on the American political landscape. Foley explains the three principles' significance to the American founding and constitutional structure. She then connects the principles to current issues as health care reform, illegal immigration, the war on terror, and internationalism"--